2019
DOI: 10.3847/1538-4357/ab4f73
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Formation and Photochemistry of Fullerene/Anthracene Cluster Cations

Abstract: Besides buckminsterfullerene (C 60 ), other fullerenes and their derivatives may also reside in space.In this work, we study the formation and photo-dissociation processes of astronomically relevant fullerene/anthracene (C 14 H 10 ) cluster cations in the gas phase. Experiments are carried out using a quadrupole ion trap (QIT) in combination with time-of-flight (TOF) mass spectrometry. The results show that fullerene (C 60 , and C 70 )/anthracene (i.e., [(C 14 H 10 ) n C 60 ] + and [(C 14 H 10 ) n C 70 ] + ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 58 publications
2
26
1
Order By: Relevance
“…In the ion-molecule reaction formation processes and the reaction evolution network, the relative reactivity of these species is very important: It affects the abundance ratio of formed species (Jäger et al 2009;Montillaud et al 2013;Zhen et al 2019). In this work, the relative reactivity of these species is initially obtained: Dehydrogenated PAH cations have a lower reactivity than carbon cluster cations, and organic molecules have a different formation behavior when reacting with PAH species.…”
Section: Discussion and Astronomical Implicationsmentioning
confidence: 99%
“…In the ion-molecule reaction formation processes and the reaction evolution network, the relative reactivity of these species is very important: It affects the abundance ratio of formed species (Jäger et al 2009;Montillaud et al 2013;Zhen et al 2019). In this work, the relative reactivity of these species is initially obtained: Dehydrogenated PAH cations have a lower reactivity than carbon cluster cations, and organic molecules have a different formation behavior when reacting with PAH species.…”
Section: Discussion and Astronomical Implicationsmentioning
confidence: 99%
“…More importantly, it is found that the IR spectra of the C 60 /anthracene adducts are similar to those of C 60 and other unidentified IR emission bands recorded by astronomical observations (García-Hernández et al, 2013). Motivated by García-Hernández et al (2013)'s work, the formation and photochemistry of (C 60 and C 70 )/anthracene cluster cations in the gas phase were investigated in this lab (Zhen et al, 2019c ). It should be mentioned that Candian et al (2019) reported a theoretical study of the stability and IR spectra of neutral and ionized fullerenes with a coverage from C 44 to C 70 .…”
Section: Introductionmentioning
confidence: 70%
“…Fullerene/PAHs adducts are one family of the fullerene reaction products and are of astrochemical interest. It is known that fullerene/PAHs adducts are generated via the Diels−Alder cycloaddition reactions (Briggs & Miller, 2006;Petrie & Bohme, 2000;Cataldo et al, 2014;Zhen et al, 2019c). On the other hand, anthracene (C 14 H 10 ) is among the simple PAH molecules, whose reaction with C 60 has received considerable attentions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,36 It is remarkable that both the bottom-up and top-down strategies to fullerenes have faced limited efficiencies under conditions prevailing in circumstellar envelopes 25 with observed abundances challenging high-temperature circumstellar reaction networks derived from the chemistry of sooty environments in hydrocarbon flames. 37 The impending involvement of PAHs within the framework of a bottom-up 38,39 and top-down 27 synthesis of circumstellar fullerenes advocates a promising link between PAHs and fullerenes considering that these are known to coexist towards, e.g., TC 1. 11 However, despite this possible connection between fullerenes and PAHs, even the synthetic routes to 'bent' PAHs such as corannulene (C20H10) in carbon rich circumstellar envelopes are still unknown.…”
Section: Introductionmentioning
confidence: 99%